Procedure-Oriented Torsional Anatomy of the Hand for Spasticity Injection. Issue 2 (March 2017) - John, Joslyn; Cianca, John; Chiou-Tan, Faye; Pandit, Sindhu; Furr-Stimming, Erin; Taber, Katherine H.
Abstract : Objectives: To provide musculoskeletal ultrasound (MSKUS) images of hand anatomy in the position of hemiparetic flexion as a reference for spasticity injections. After a stroke, spasticity can result in anatomic distortion of the hand. Spasticity may require treatment with botulinum toxin or phenol injections. Anatomic distortion may decrease the accuracy of injections. Standard anatomic references are of limited utility because they are not in this spastic hemiparetic position. There presently is no anatomic reference in the literature for these spastic postures. This study is part three of a series examining torsional anatomy of the body. Design: Ultrasound (US) images were obtained in a healthy subject. The muscles examined included the lumbricals and the flexor pollicis brevis. A marker dot was placed at each dorsal and palmar anatomic injection site for these muscles. The US probe was placed on these dots to obtain a cross-sectional view. A pair of US images was recorded with and without power Doppler imaging: the first in anatomic neutral and second in hemiparetic spastic positions. In addition, a video recording of the movement of the muscles during this rotation was made at each site. Results: On the palmar view, the lumbricals rotated medially. On dorsal view, the lumbricals can be seen deep to the dorsal interossei muscles, with spastic position, and they become difficult to identify. The flexor pollicis brevis (FPB) muscle contracts with torsion, making abductor pollicis brevis (APB) predominately in view. Discussion: The anatomic location of the lumbrical muscles makes them difficult to inject even with ultrasound guidance. However, recognizing the nearby digital vasculature allows for improved identification of the musculature for injection purposes. The FPB muscle also can be identified by its adjacent radial artery lateral to the flexor pollicus longus tendon. Conclusion: Normal anatomy of hand can become distorted in spastic hemiparesis. Diagnostic ultrasound is able to discern these anatomic locations if the sonographer is competent in recognizing the appearance of normal anatomy and is skilled in resolving the visual changes that occur in spastic hemiparesis. The authors hope this series of images will increase the accuracy, safety, and efficacy of spasticity injections in the hand.